2022
DOI: 10.3389/fphar.2022.980391
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of statin adherence in primary cardiovascular disease prevention during the pandemic

Abstract: Background: Study of medication adherence patterns can help identify patients who would benefit from effective interventions to improve adherence.Objectives: To identify and compare groups of statin users based on their adherence patterns before and during the COVID-19 pandemic, to characterize the profile of users in each group, and to analyze predictors of distinct adherence patterns.Methods: Participants of the CARhES (CArdiovascular Risk factors for HEalth Services research) cohort, comprising individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…However, if the impact of the COVID-19 epidemic on interruptions of antihypertensive treatment has been little assessed, several studies have shown a worrying decrease in the use of chronic drugs over the pandemic, in fields as various as mental disorders ( Mansfield et al, 2021 ; Sanchez et al, 2022 ) or diabetes for instance ( Corral-Partearroyo et al, 2022 ; Mathieu et al, 2022 ). Considering more specifically cardiovascular drugs, our results appear consistent with those of a study assessing the impact of the epidemic on adherence to statins ( Malo et al, 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…However, if the impact of the COVID-19 epidemic on interruptions of antihypertensive treatment has been little assessed, several studies have shown a worrying decrease in the use of chronic drugs over the pandemic, in fields as various as mental disorders ( Mansfield et al, 2021 ; Sanchez et al, 2022 ) or diabetes for instance ( Corral-Partearroyo et al, 2022 ; Mathieu et al, 2022 ). Considering more specifically cardiovascular drugs, our results appear consistent with those of a study assessing the impact of the epidemic on adherence to statins ( Malo et al, 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…Our hypothesis was that stratified medicine using mechanistically targeted medical therapy would improve modifiable risk factors, such as blood pressure, body mass index, hyperlipidemia, and cigarette smoking. However, most of the patients participated during the COVID-19 pandemic that caused restrictions on access to primary 26,27 and secondary medical care, reduced adherence with medication, 28 reduced control of cardiovascular risk factors, 29,30 and enhanced unfavorable social behaviors. 31 During the pandemic, reduced access undermined the feasibility of medical management in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, it is crucial to recognize the impact of the COVID-19 pandemic on the management and behaviour of individuals with risk factors for CVD. We conducted a study 31 to compare adherence patterns before and during the COVID-19 pandemic among individuals who were first prescribed statins for primary CVD prevention. The study findings revealed the presence of four distinct trajectories of statin adherence across the pandemic.…”
Section: What Has It Found?mentioning
confidence: 99%